2013
DOI: 10.1063/1.4829769
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of liquid-vapor coexistence of confined quantum fluids

Abstract: The liquid-vapor coexistence (LV) of bulk and confined quantum fluids has been studied by Monte Carlo computer simulation for particles interacting via a semiclassical effective pair potential Veff(r) = VLJ + VQ, where VLJ is the Lennard-Jones 12-6 potential (LJ) and VQ is the first-order Wigner-Kirkwood (WK-1) quantum potential, that depends on β = 1∕kT and de Boer's quantumness parameter Λ=h/σ√mε, where k and h are the Boltzmann's and Planck's constants, respectively, m is the particle's mass, T is the tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…This is a well-established approach for classical Mie fluids. [66][67][68] Previous work 13 has suggested that the LJ-FH1 potential yields an accurate representation of the VLE envelope of neon, normal hydrogen, and helium. By performing GEMC simulations with the same potentials, we were able to reproduce their simulation results for neon and hydrogen, but obtained different results for helium.…”
Section: General Discussion Of Feynman-hibbs Correctionsmentioning
confidence: 99%
See 4 more Smart Citations
“…This is a well-established approach for classical Mie fluids. [66][67][68] Previous work 13 has suggested that the LJ-FH1 potential yields an accurate representation of the VLE envelope of neon, normal hydrogen, and helium. By performing GEMC simulations with the same potentials, we were able to reproduce their simulation results for neon and hydrogen, but obtained different results for helium.…”
Section: General Discussion Of Feynman-hibbs Correctionsmentioning
confidence: 99%
“…Theory and simulation studies based on these effective potentials have established them as successful in accounting for quantum corrections. 8,10,11,13,32,33 The complete expression for the quantum-corrected Mie-FH2 potential between particles of type i and j is…”
Section: A the Influence Of Quantum Effects On The Interaction Potenmentioning
confidence: 99%
See 3 more Smart Citations